2018
DOI: 10.1007/s10461-018-2298-8
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable at Each Step in the PMTCT Care Cascade: High Loss to Follow Up During Pregnancy and the Postpartum Period in Tanzania

Abstract: Objective: In 2013, Tanzania adopted the World Health Organization's Option B+ guidelines for prevention of mother-to-child transmission of HIV (PMTCT), whereby all HIV-infected pregnant women initiate lifelong antiretroviral therapy. This study examined retention in PMTCT across critical junctures in the care continuum.Methods: This was a retrospective study of patient-level data for a cohort of women enrolled in PMTCT during the first year of Option B+ in Tanzania. Retention in care was described across thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
(37 reference statements)
4
23
1
Order By: Relevance
“…Hence, initiating ART on the same day with HIV diagnosis or under the "test and treat" approach increases the risk of LTFU from the program [27,28]. The risk of LTFU among women who were newly diagnosed with HIV was consistently higher than women who were previously diagnosed with HIV [25,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, initiating ART on the same day with HIV diagnosis or under the "test and treat" approach increases the risk of LTFU from the program [27,28]. The risk of LTFU among women who were newly diagnosed with HIV was consistently higher than women who were previously diagnosed with HIV [25,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, the clinics struggle to trace patients after delivery due to wrong addresses. This was confirmed in another study whereby travel was three times more common after delivery than before delivery (18,23,24). Both healthcare providers and patients also agreed that HIV disclosure facilitates care by allowing for family support (16,17,25).…”
Section: Discussionmentioning
confidence: 79%
“…In another study, it was reported that women who had a new HIV diagnosis were more likely to be loss to follow up than women with an established HIV diagnosis (17,18). This shows that intensive counselling and support system is of importance during ANC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 A recent study of retention in care during the first year of the B+ programme in Tanzania found that 2 years after enrolment into the B+ programme, 59% of women were LTFU, and nearly one-third of those lost, were lost during pregnancy. 35 A qualitative study carried out among women referred for life-long antiretroviral therapy from the ComTru study indicated that among the main deterrents from reporting were fear of stigmatisation and conflicts with work resulting from frequent clinic visits and potentially resulting in loss of income. These deterrents have also been found to affect clinic attendance among women receiving option B+ in South Africa.…”
Section: Discussionmentioning
confidence: 99%